Frequent Infection of Cats With SARS-CoV-2 Irrespective of Pre-Existing Enzootic Coronavirus Immunity, Brazil 2020 - Oliveira-Filho, Edmilson F. de; de Carvalho, Otávio V.; Carneiro, Ianei O.; Fernandes, Fagner D’ambroso; Vaz, Sara Nunes; Pedroso, Célia; Gonzalez-Auza, Lilian; Urbieta, Victor Carvalho; Kühne, Arne; Mayoral, Rafaela; Jo, Wendy K.; Moreira-Soto, Andrés; et al. (Frontiers in Immunology, 2022)
Carnivores such as cats and minks are highly susceptible to SARS-CoV-2. Brazil is a global COVID-19 hot spot and several cases of human-to-cat transmission have been documented. We investigated the spread of SARS-CoV-2 by testing 547 domestic cats sampled between July-November 2020 from seven states in southern, southeastern, and northeastern Brazil. Moreover, we investigated whether antibodies elicited by enzootic coronaviruses affect SARS-CoV-2 infection in cats. We found significantly higher neutralizing antibody titers against the Gamma variant of concern than against an early SARS-CoV-2 isolate (p=0.001), validating the use of Gamma for further testing. The overall SARS-CoV-2 seroprevalence validated by plaque reduction neutralization test (PRNT90) was 7.3% (95% CI, 5.3-9.8). There was no significant difference in SARS-CoV-2 seroprevalence between Brazilian states, suggesting homogeneous infection levels ranging from 4.6% (95% CI, 2.2-8.4) to 10.8% (95% CI, 6.4-16.7; p=0.4438). Seroprevalence of the prototypic cat coronavirus Feline coronavirus (FCoV) in a PRNT90 was 33.3% (95% CI, 24.9-42.5) and seroprevalence of Bovine coronavirus (BCoV) was 1.7% (95% CI, 0.2-5.9) in a PRNT90. Neutralizing antibody titers were significantly lower for FCoV than for SARS-CoV-2 (p=0.0001), consistent with relatively more recent infection of cats with SARS-CoV-2. Neither SARS-CoV-2 antibody titers (p=0.6390), nor SARS-CoV-2 infection status were affected by FCoV serostatus (p=0.8863). Our data suggest that pre-existing immunity against enzootic coronaviruses neither prevents, nor enhances SARS-CoV-2 infection in cats. High seroprevalence substantiates frequent infection of domestic cats and raises concerns on potential SARS-CoV-2 mutations escaping human immunity upon spillback.